Legal Responsibility for Medical Risks, Medical Errors, and Malpractice in Health Services - Diah Arimbi (APPTHI, 2025)
Disputes in medical care are often difficult to resolve due to the legal, ethical, and complex aspects of proving the case. It is not uncommon for medical procedures that do not meet patients' expectations to be attributed to medical error, when in fact they may be caused by unavoidable medical risks. This study aims to assess and differentiate between medical risks, medical errors, and malpractice, and to understand their legal liability. The method used is a normative-juridical approach with descriptive-analytical specifications. Data were collected through literature review and analyzed qualitatively and normatively. The results indicate that medical risks are part of healthcare services that may be unavoidable, unlike medical negligence, which involves an element of error. While medical errors and malpractice have fundamental differences, in legal practice, they are often difficult to distinguish. Medical errors are unintentional mistakes, while malpractice involves negligence or disregard for professional standards. A clear understanding of these three concepts is crucial to prevent the criminalization of medical personnel who work according to procedures and to provide balanced legal protection for patients and healthcare providers.